2010
DOI: 10.1038/oby.2009.358
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory SNP in the RBP4 Gene Modified the Expression in Adipocytes and Associated With BMI

Abstract: Retinol‐binding protein 4 (RBP4) is a recently identified adipokine that was involved in insulin resistance. RBP4 is predominantly expressed from the liver in normal metabolic state to transport retinoids throughout the body, but the exact physiological function and the regulatory mechanisms of adipocyte‐derived RBP4 have not been revealed. We conducted the genetic analysis about metabolic parameters in Japanese and Mongolian; the minor allele carriers of regulatory single‐nucleotide polymorphism (SNP −803G>A)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
4
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 37 publications
2
47
4
1
Order By: Relevance
“…This appears to be more than a spurious correlation, since recent studies have demonstrated that RBP4 is an adipokine (adipose-derived cytokine) with retinoid-independent, proinflammatory activity that contributes to the development of insulin resistance (13,(19)(20)(21). Moreover, a human single nucleotide polymorphism that increases RBP4 promoter activity confers a 2-fold increase for the risk of type 2 diabetes (22,23).…”
Section: S Erum Retinol-binding Protein 4 (Rbp4) Is the Sole Specificmentioning
confidence: 99%
“…This appears to be more than a spurious correlation, since recent studies have demonstrated that RBP4 is an adipokine (adipose-derived cytokine) with retinoid-independent, proinflammatory activity that contributes to the development of insulin resistance (13,(19)(20)(21). Moreover, a human single nucleotide polymorphism that increases RBP4 promoter activity confers a 2-fold increase for the risk of type 2 diabetes (22,23).…”
Section: S Erum Retinol-binding Protein 4 (Rbp4) Is the Sole Specificmentioning
confidence: 99%
“…Two SNPs (SNP (risk allele) rs10882283(G) and rs10882273(C)) are associated with increased BMI and waist-to-hip ratio (33). Regulatory RBP4 SNP (SNP (risk allele) rs3758539(A)) resulting in overexpression of RBP4 and increased susceptibility for obesity, as a consequence of increased adipogenesis, has been reported (34). In addition, a higher visceral RBP4 mRNA expression has been reported in diabetes risk RBP4 haplotype carriers (SNP (risk allele) rs3758539(G), c.248C44TOC, rs12265684(G), and rs10882273(C)) (33).…”
Section: Characteristics Of Rbp4mentioning
confidence: 99%
“…The tissues were immediately transported to the laboratory in ice-cold saline, frozen in liquid nitrogen within 10 min of collection, and stored at 80 until the experiment, as reported previously 31) .…”
Section: Biopsy Of Adipose Tissuesmentioning
confidence: 99%